2020
DOI: 10.1002/bit.27352
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent indicators for continuous and lineage‐specific reporting of cell‐cycle phases in human pluripotent stem cells

Abstract: Proper cell‐cycle progression is essential for the self‐renewal and differentiation of human pluripotent stem cells (hPSCs). The fluorescent ubiquitination‐based cell‐cycle indicator (FUCCI) has allowed the dual‐color visualization of the G1 and S/G2/M phases in various dynamic models, but its application in hPSCs is not widely reported. In addition, lineage‐specific FUCCI reporters have not yet been developed to analyze complex tissue‐specific cell‐cycle progression during hPSC differentiation. Desiring a rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Donor plasmid construction. The donor plasmids targeting AAVS1 locus were constructed as previously described (Chang et al, 2020). Briefly, to generate the CAG-IL13 T-CAR plasmid, the TQM-IL13 CAR fragment (Kim et al, 2020b) Maintenance and differentiation of hPSCs.…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor plasmid construction. The donor plasmids targeting AAVS1 locus were constructed as previously described (Chang et al, 2020). Briefly, to generate the CAG-IL13 T-CAR plasmid, the TQM-IL13 CAR fragment (Kim et al, 2020b) Maintenance and differentiation of hPSCs.…”
Section: Methods Detailsmentioning
confidence: 99%
“…The donor plasmids targeting AAVS1 locus were constructed as previously described (Chang, et al, 2020). Briefly, to generate the CAG-IL13 T-CAR plasmid, the TQM-IL13 CAR fragment (Kim et al, 2020b) was amplified from Addgene plasmid #154054 and then cloned into the AAVS1-Puro CAG-FUCCI donor plasmid (Addgene; #136934), replacing the FUCCI.…”
Section: Methodsmentioning
confidence: 99%
“…H9 wildtype hPSCs were obtained from WiCell and maintained on Matrigel‐coated 6‐well plate in mTeSR1 or mTeSR plus medium. To make OptoWnt H9 cells, Cry2‐LRP6c‐2A‐mCherry construct was cloned into AAVS1 donor plasmid (Addgene #80945) and nucleofected into H9 hPSCs along with Cas9/AAVS1 gRNA plasmid 24 . Puromycin‐resistant mCherry+ hPSC colonies were picked and genotyped for homozygosity.…”
Section: Methodsmentioning
confidence: 99%
“…To make OptoWnt H9 cells, Cry2-LRP6c-2A-mCherry construct was cloned into AAVS1 donor plasmid (Addgene #80945) and nucleofected into H9 hPSCs along with Cas9/AAVS1 gRNA plasmid. 24 Puromycinresistant mCherry+ hPSC colonies were picked and genotyped for homozygosity. The resulting OptoWnt hPSCs were maintained in dark (foil cover) and used for the downstream applications.…”
Section: Stem Cell Culture and Genome Editingmentioning
confidence: 99%
“…Interestingly, the use of the FUCCI cell cycle reporter revealed that small molecule regulators of PPARd signaling could modulate the cardiomyocyte cell cycle [ 125 ]. Furthermore, in vivo models [ 126 , 127 ] and hiPS-derived cardiomyocytes [ 128 ] have been generated to study cell cycle progression in the heart using FUCCI indicators. Interestingly, a recent study generated a Ki67-based lineage and traced mice to track the cell cycle activation in cardiomyocytes [ 129 ].…”
Section: Recent Genetic Tools To Track Cardiomyocyte Cell Cyclingmentioning
confidence: 99%